PD-L1-Expressing Dendritic Cells Contribute to Viral Resistance during Acute HSV-1 Infection - Katie M. Bryant-Hudson; Daniel J. J. Carr (Clinical and Developmental Immunology)
The inhibitory receptor, Programmed Death 1 (PD-1), and its ligands (PD-L1/PD-L2) are thought to play a role in immune surveillance during chronic viral infection. The contribution of the receptor/ligand pair during an acute infection is less understood. To determine the role of PD-L1 and PD-L2 during acute ocular herpes simplex virus type 1 (HSV-1) infection, HSV-1-infected mice administered neutralizing antibody to PD-L1 or PD-L2 were assessed for viral burden and host cellular immune responses. Virus titers were elevated in cornea and trigeminal ganglia (TG) of anti-PD-L1-treated mice which corresponded with a reduced number of CD80-expressing dendritic cells, PD-L1+ dendritic cells, and HSV-1-specific CD8+ T cells within the draining (mandibular) lymph node (MLN). In contrast, anti-PD-L2 treatment had no effect on viral replication or changes in the MLN population. Notably, analysis of CD11c-enriched MLN cells from anti-PD-L1-treated mice revealed impaired functional capabilities. These studies indicate PD-L1-expressing dendritic cells are important for antiviral defense during acute HSV-1 infection.